Combined crossed molecular beams and computational study on the N(2D) + HCCCN(X1Σ+) reaction and implications for extra-terrestrial environments. (17th January 2022) - Liang, Pengxiao; Mancini, Luca; Marchione, Demian; Vanuzzo, Gianmarco; Ferlin, Francesco; Recio, Pedro; Tan, Yuxin; Pannacci, Giacomo; Vaccaro, Luigi; Rosi, Marzio; Casavecchia, Piergiorgio; Balucani, Nadia
Abstract : The reaction of the nitrogen atom (N) in its first electronically excited state ( 2 D) with cyanoacetylene (HC3 N) has been investigated under single-collision conditions by using the crossed molecular beam method with mass spectrometric detection at a collision energy of 31 kJ mol −1 . With the support of electronic structure calculations, we found that this reaction proceeds via the barrierless addition of the N( 2 D) atom to the carbon–carbon triple bond of HC3 N, followed by the formation of a cyclic intermediate adduct HC(N)CCN, which dissociates to C(N)CCN + H products or isomerises to a more stable intermediate HNCCCN by H-migration and ring-opening processes. The long-lived HNCCCN complex produces the linear 3 Σg – ground state dicyanocarbene (NCCCN) radical plus atomic hydrogen through a barrierless unimolecular dissociation accompanied by a negligible competitive channel forming the NCCCN radical ( 1 A1 ) with a bent C 2 v structure plus H. The main product of this neutral-neutral reaction is the 3 NCCCN radical that could be a potential precursor to form other nitriles (C2 N2, C3 N) or more complex organic species in planetary atmospheres, such as that of Titan and Pluto, in cometary comas, and in UV irradiated interstellar environments. GRAPHICAL ABSTRACT: UF0001